2019
DOI: 10.1038/s41598-019-47463-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Purification of Terbium-155 from Pseudo-Isobaric Impurities in a Mass Separated Source Produced at CERN

Abstract: Four terbium radioisotopes ( 149, 152, 155, 161 Tb) constitute a potential theranostic quartet for cancer treatment but require any derived radiopharmaceutical to be essentially free of impurities. Terbium-155 prepared by proton irradiation and on-line mass separation at the CERN-ISOLDE and CERN-MEDICIS facilities contains radioactive 139 Ce 16 O and also zinc or gold, depending on the catcher foil used. A method using ion-exchange and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
(33 reference statements)
1
13
1
Order By: Relevance
“…The pseudo-isobars 133 CeO + and 133 LaO + were eluted at the end. A similar study on the chemical separation of155 Tb from pseudo-isobaric 139 Ce16 O was reported by Webster et al(61). In this study, sodium bromate was used to oxidize Ce(II) to Ce(IV).…”
supporting
confidence: 63%
“…The pseudo-isobars 133 CeO + and 133 LaO + were eluted at the end. A similar study on the chemical separation of155 Tb from pseudo-isobaric 139 Ce16 O was reported by Webster et al(61). In this study, sodium bromate was used to oxidize Ce(II) to Ce(IV).…”
supporting
confidence: 63%
“…The same concern exists for other stable (e.g. 139 La 16 O, 155 Gd) or radioactive ( 155 Eu) impurities [11]. Similar conditions were observed for the shorter-lived isotope 149 Tb, also produced at ISOLDE, where isobaric contaminants 149 Eu and 133 Ce 16 O are limiting the sample purity [12].…”
Section: Introductionmentioning
confidence: 64%
“…Lanthanides are represented, as many of their easily accessible chemically similar -and thus interchangeableradioisotopes constitute versatile agents for diagnostics and therapy. The purification of SPECT isotope 155 Tb (5.3 d) is featured 29 , and a method for the production and recovery of the theranostic pair 132,135 La (4.8 h and 19.5 h) with initial imaging and biodistribution evaluation is reported 30 . Alpha emitter 225 Ac (10.0 d) has emerged as a TAT isotope: one contribution looks into the in-vivo redistribution of 225 Ac daughter isotopes in a mouse model 31 ; another study reports the purification of accelerator produced 225 Ac using a silicotitanate sorbent 32 .…”
Section: Collection Overviewmentioning
confidence: 99%